Design of Modified Complementary Terminal Sliding Mode Controller for Wind Turbine at Region Ii Using a Two-Mass Model - Diaz-Diaz, M; Rajendran, S (Elsevier B.V., 2024)
Mechanical loads impact the life span of a wind turbine; therefore, the reduction of transient loads in the drive train has gained more emphasis during the design of the controller for power extraction. The trade-off between power extraction and load reduction on the drive train has become a critical concern for wind turbines. Existing control approaches improve energy extraction and impose a more significant transient load on the drive train. Therefore, to address the above issue, a modified complementary terminal sliding mode controller is proposed in this study for wind turbines at below-rated wind speeds. The performance of both the proposed and existing controllers has been tested with a 600 kW FAST simulator. Moreover, each controller has been examined using different wind spectral models, such as Kaimal, Von Karman, Smooth-Terrain, and NWTCUP. The turbulent intensities of these models varied from 5% to 25%, and average wind speeds ranged from 7 m/s to 8.5 m/s. A dSPACE 1202 board was used to test the efficacy of the proposed controller in real-time. This analysis indicates that the proposed controller reduces the transient load by 11.98% and the control input by 9.57% compared to the complementary terminal sliding mode controller. Additionally, the proposed controller improves the energy capture by 1.18%. Finally, this analysis shows that the proposed approach can enhance overall performance and capture maximum power at below-rated wind speeds compared to existing control schemes. © 2024 The Authors